Removal of sulfur compounds from oxidized diesel fuel using activated carbon and alumina adsorbents - Samaniego, Marvin L. (College of Engineering, University of the Philippines Diliman, 2013)
Sulfur compounds in fossil fuels are responsible for various toxic emissions during combustion. More stringent regulations render conventional hydrodesulfurization inadequate. In this study, oxidative-adsorptive desulfurization was applied to remove sulfur from real diesel. Oxidative- adsorptive desulfurization has been considered as the most cost-effective alternative to hydrodesulfurization. Commercial grade activated carbon (AC) and alumina were used to separate oxidized sulfur compounds (OSC) from the diesel. For both adsorbents, the pseudo-second order kinetic model (0.9999 and 0.9944) best describe OSC removal. The kinetic rate constant, k₂ for AC and alumina adsorbent were 0.0431 and 0.5001 g/mg min, respectively. OSC removal by AC and alumina was characterized by Langmuir (0.9020) and Freundlich (0.8626) isotherm, respectively. In addition, the effect of adsorbent dosage, reaction temperature, and initial sulfur concentration were investigated. Adsorption capacities increased with adsorbent dosage and initial sulfur concentration. Moreover, the adsorption activation energy, Ea, enthalpy of activation, ΔH, and entropy of activation, ΔS for alumina were 17.559 kJ/mol, 0.558 kJ/mol, and -8.482 J/mol, respectively. The low values of Ea (<40 kJ/mol) and Gibb's free energy (<20 kJ/mol) indicate physical adsorption. On the other hand, the negative activation energy value of -21.71 kJ/mol suggests that the rise in solution temperature did not favor OSC adsorption on AC. FTIR analysis of adsorbents show that aromatic compounds in diesel fuel compete with sulfur compounds for adsorption sites. Overall, AC and alumina were found effective adsorbents for OSCs in diesel fuel.